Analisis Kesalahan Ejaan dalam Naskah Pidato Politik Megawati di Kongres VI PDI Perjuangan - Permadi, M.B.Putrajurit; Yussriyyah W, Yasmine; Sidalle, Anselmus; Kurniawan, Eva Dwi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze spelling errors in Megawati Soekarnoputri's political speech at the 6th Indonesian Democratic Party of Struggle (PDI-P) Congress. This study uses a descriptive qualitative approach, using speech manuscripts as data sources accessed through the official PDI-P website for East Java. The research data consists of linguistic units in the speech manuscript containing spelling errors. Data collection was conducted through documentation using reading and note-taking techniques, while data analysis was conducted by identifying, classifying, and describing spelling errors based on the Indonesian Spelling Rules (EYD V) and the Big Indonesian Dictionary (KBBI). The results showed that 14 spelling errors were found in the speech manuscript. The spelling errors found included the use of non-standard words, typos, omissions, additions, and word separation errors. These findings indicate that the application of standard Indonesian spelling in political speeches still needs improvement to comply with applicable linguistic standards.